The influence of e-service quality and e-trust on e-customer loyalty with e-customer satisfaction as a mediating variable - Tri Lestari (Law and Economics, 2026)
Customer loyalty contributes substantially to organizational performance and long-term business sustainability. The development of loyalty is closely associated with customers’ experiences and the quality of interactions established by an organization. This research examines the roles of e-service quality and e-trust in shaping e-customer loyalty while considering e-customer satisfaction as an intervening construct. Information was obtained from 100 Brainy Kids Indonesia partners through a questionnaire survey and subsequently analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach with Smart PLS 3. The results indicate that e-service quality and e-trust positively affect both e-customer satisfaction and e-customer loyalty. Furthermore, e-customer satisfaction contributes to the enhancement of customer loyalty and serves as an intermediary mechanism linking e-service quality and e-trust with e-customer loyalty. The findings underscore the importance of maintaining high electronic service quality and strengthening customer trust as strategic efforts to improve satisfaction and foster long-term customer loyalty